Design and construction of a battery cycler - Castillo Ocaña, Guido (2021)
The objective of the present work is to design and build a device "The Battery Cycler" whose function is to automatically and repeatedly charge and discharge a battery and store the data of the battery voltage and current intensity as a function of time for each charging and discharging process, with these data the state of charge, coulombic efficiency and energy efficiency of the battery can be determined. The state of charge of the battery is an important parameter that indicates how much charge is available in the battery with respect to its capacity, the precise estimation of the state of charge of the battery is essential in a battery management system, as it allows to avoid an overcharge or deep discharge of the battery, conditions that can irreversibly damage the battery.